Emergency: a theoretical analysis in domestic and foreign science - I. A. Gorbushina (Вестник Северо-Кавказского федерального университета)
The focus of this article is on the theoretical analysis of the concepts developed by Russian and foreign scientists regarding emergencies. When analyzing the concepts of emergencies the author defines its components that make it a social category. There is also a new definition for emergency offered